Supervisi Akademik Pengawas Sekolah Dalam Meningkatkan Profesionalisme Guru Di Masa Pandemi Covid-19 Tahun 2020/2021 - Sudarman Sudarman (LPMP Provinsi DKI Jakarta, 2021)
This research was motivated by the low professionalism of teachers SMPN 228 Jakarta during Covid-19 Pandemic. The purpose of this study to improve teachers professionalism of SMPN 228 Jakarta during Covid-19 pandemic. This research is a school action research (PTS) which is conducted through socialization through the Teacher Working Group (KKG). Design of this study uses a non-directive supervision model, which consists of four stages, namely: planning, action, observation and reflection. Data analysis technique was carried out in a descriptive qualitative manner. Results of this study indicate that teachers professionalism of SMPN 228 Jakarta during Covid-19 pandemic has increased, namely from the results of academic supervision carried-out on teachers of SMPN 228 Jakarta there is an increase in teacher professionalism in online learning. Teachers in previous learning still have difficulty adapting to online learning, after coaching and supervision, teachers are used to developing their professionalism in online learning